Impact of Covid’19 in real estate sector of Bangladesh: A case study of Amin Mohammad Group - Anan, Afra Ramisa (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.